Diagnóstico de la problemática de emisiones de gases de efecto invernadero del grupo de trabajo de Inspección y Vigilancia de Reglamentos Técnicos de la Superintendencia de Industria y Comercio al año 2021 - Arévalo Beltrán, Camila Alejandra; Jaimes Tamayo, Estefan (Universidad Antonio Nariño, 2023)
In response to the commitments made by governments to reduce greenhouse gases, the public and private sectors have chosen to implement strategies that contribute to achieving this objective. In this project, a diagnosis was developed regarding the problem of greenhouse gas emissions in the Superintendence of Industry and Commerce, focusing on the activities carried out by the Inspection and Surveillance of Technical Regulations working group in the validity of the year 2021